Pathologic and Treatment Outcomes Among a Geriatric Population of Endometrial Cancer Patients: An NRG Oncology/Gynecologic Oncology Group Ancillary Data Analysis of LAP2. Issue 4 (1st May 2017) - Bishop, Erin A.; Java, James J.; Moore, Kathleen N.; Walker, Joan L.
Abstract : Objectives: Elderly endometrial cancer patients have worse disease-specific survival than their younger counterparts, but the cause for this discrepancy is unknown. The goal of this analysis is to compare outcomes by age in a fully staged elderly endometrial cancer population. Methods/Materials: This is an analysis of patients on Gynecologic Oncology Group Study (GOG) LAP2, which included clinically early stage endometrial cancer patients randomized to laparotomy versus laparoscopy for surgical staging. Patients were divided into risk groups based on criteria defined by GOG protocol 99. Differences in outcomes and adjuvant therapy were assessed within these risk groups. Results: LAP2 included 715 patients 70 years or older. With increasing age, worse tumor characteristics were seen. Older patients received similar rates of adjuvant therapy when stratified by stage. Patients 70 years or older had significantly worse progression-free survival and overall survival, and on multivariate analysis, older age and high-risk uterine factors were predictors of progression-free survival and overall survival, whereas stage and lymph node metastases were not. When patients were divided into GOG protocol 99 risk categories, most of those who met the high-intermediate risk criteria did so based on age above 70 years and grade 2 to 3 disease. These patients had low risk of recurrence (3.3%) compared with those who met the criteria by age above 70 years and all 3 uterine factors (20.9%). Conclusions: In early stage endometrial cancer, patients 70 years or older who undergo similar surgical management and adjuvant therapy, age and tumor characteristics independently predict recurrence. Most patients older than 70 years meet the high-intermediate risk criteria for recurrence based on age and 1 other uterine risk factor, and our results suggest that these patients are at low risk for recurrence.